Thyroid hormone system disrupting chemicals. Issue 5 (September 2021) - Köhrle, Josef; Frädrich, Caroline
Abstract : The thyroid hormone system is a main target of endocrine disruptor compounds (EDC) at all levels of its intricately fine-tuned feedback regulation, synthesis, distribution, metabolism and action of the 'prohormone' thyroxine and its active metabolites. Apart from classical antithyroid effects of EDC on the gland, the majority of known and suspected effects occurs at the pre-receptor control of T3 ligand availability to T3 receptors exerting ligand modulated thyroid hormone action. Tissue-, organ- and cell-specific expression and function of thyroid hormone transporters, deiodinases, metabolizing enzymes and T3-receptor forms, all integral components of the system, may mediate adverse EDC effects. Established evidence from nutritional, pharmacological and molecular genetic studies clearly support the functional, biological, and clinical relevance of these targets. Iodine-containing thyroid hormones and the organization of this system are highly conserved during evolution from primitive aquatic life forms, amphibia, birds throughout all vertebrates including humans. Mechanistic studies from various animal experimental models strongly support cause–effect relationships upon EDC exposure, hazards and adverse effects of EDC across various species. Retrospective case–control, cohort and population studies linking EDC exposure with epidemiological data on thyroid hormone-related (dys-)functions provide clear evidence that human development, especially of the fetal and neonatal brain, growth, differentiation and metabolic processes in adult and aging humans are at risk for adverse EDC effects. Considering that more than half of the world population still lives on inadequate iodine supply, the additional ubiquitous exposure to EDC and their mixtures is an additional threat for the essential thyroid hormone system, the health of the human population and their future progenies, animal life forms and our global environment.